A systematic review of mathematical models of the Ebola virus disease. (3rd September 2022) - Abdalla, Suliman Jamiel M.; Chirove, Faraimunashe; Govinder, Keshlan S.
ABSTRACT: Several studies have surveyed the literature of mathematical modelling of the Ebola virus disease (EVD). However, most of these reviews did not report any work published after January 2016. Furthermore, those that have considered such work focused on particular types of models, presented only findings for some models, or included just a few articles published in 2016. Additionally, these reviews did not focus on examining models by systematically identifying advantages and limitations. In light of this, we conduct a systematic review of mathematical models of EVD. We focus on the PubMed publications between January 2016 and December 2018. The objectives of this review are to present an overview of the mathematical modelling literature on EVD, identify gaps, and improve prospective models by addressing current models' constraints. The reported studies are categorised broadly in terms of the modelling approaches, model conclusions and constraints. Crucial modelling gaps are identified, and future research motivated.